Emotion Recognition of Foreign Language Teachers in College English Classroom Teaching - Li, Lei (Frontiers in Psychology, 2021)
In order to improve students' learning effect, more and more universities favor foreign language teachers who are native speakers of English. Based on the analysis and summary of the research status of emotion recognition, this paper proposes that in college English classroom teaching, foreign language teachers can reduce the communication barriers with Chinese students through emotion recognition. Based on literature review and actual situation investigation, this study identified four influencing factors on emotion recognition of foreign language teachers, namely, interactive action, facial expression, vocal emotion and body posture. In our opinion, in the teaching process, teachers can adjust the four factors of emotion recognition to achieve better teaching effect. Further, improve students' learning efficiency. Analytic Hierarchy Process (AHP) is chosen as the research method in this study. After building the analysis model, we collected the questionnaire using the Questionnaire Star, and finally got 12 valid data. After determining the importance of different factors by pairwise comparison, we draw the following conclusions: The influence degree of emotion recognition factors of foreign language teachers is in descending order: interactive action (43%), facial expression (28%), vocal emotion (21%) and body posture (9%). In the English classroom, our research provides insights into the choice of teaching methods for foreign language teachers. By adjusting emotion recognition factors, students can achieve better learning results. Finally, we provide suggestions on emotion recognition for foreign language teachers from three aspects: interactive actions, facial expressions and vocal emotions.